2009
DOI: 10.1088/0031-9155/54/18/001
|View full text |Cite
|
Sign up to set email alerts
|

The design, physical properties and clinical utility of an iris collimator for robotic radiosurgery

Abstract: Robotic radiosurgery using more than one circular collimator can improve treatment plan quality and reduce total monitor units (MU). The rationale for an iris collimator that allows the field size to be varied during treatment delivery is to enable the benefits of multiple-field-size treatments to be realized with no increase in treatment time due to collimator exchange or multiple traversals of the robotic manipulator by allowing each beam to be delivered with any desired field size during a single traversal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 15 publications
3
102
0
1
Order By: Relevance
“…These results, which were supported by equivalent SRS diode measurements, were consistent with those of a previous investigation in which FWHM and penumbra values for fixed cones and the Iris were found to be in substantial agreement, with a maximum discrepancy of 0.2 mm in penumbra width for the 5 mm diameter 36. By the vendor's technical specifications, the average penumbra for the Iris is expected to be larger by 0.2 to 0.6 mm than that for the equivalent fixed cone and to increase with field size, a consequence of the stepwise approximation of a divergent collimator shape because of the increase in transmission penumbra 3. To our knowledge, no other intercomparison between Iris and fixed cones collimator dose profiles exists in the literature.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…These results, which were supported by equivalent SRS diode measurements, were consistent with those of a previous investigation in which FWHM and penumbra values for fixed cones and the Iris were found to be in substantial agreement, with a maximum discrepancy of 0.2 mm in penumbra width for the 5 mm diameter 36. By the vendor's technical specifications, the average penumbra for the Iris is expected to be larger by 0.2 to 0.6 mm than that for the equivalent fixed cone and to increase with field size, a consequence of the stepwise approximation of a divergent collimator shape because of the increase in transmission penumbra 3. To our knowledge, no other intercomparison between Iris and fixed cones collimator dose profiles exists in the literature.…”
Section: Discussionmentioning
confidence: 98%
“…The Iris collimator is designed to achieve an aperture reproducibility of 0.2 mm at 800 mm SDD,3 with the current recommendation (Accuray Physics Essentials Guide 2012, P/N 1023868‐ENG A) for QA suggesting monthly film measurements of all 12 field sizes. Nonequivalent DPs reproducibility after a reset of the Iris aperture were found to be accurate within 2% for all profiles, with a maximum discrepancy of 1.9% for the 5 mm diameter in‐plane profile (<0.1 mm) and of 1% for the 10 mm diameter in plane and cross‐plane profiles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We expect that there are two likely causes of these results: the reproducibility of the leaf position of the MLC and the dependence of the MLC beam modeling accuracy on the TPS. Concerning the collimator position reproducibility, a variable collimator is designed to achieve an aperture reproducibility of ≤0.2 mm at a SAD of 800 mm 25. Meanwhile, Fürweger et al demonstrated using Bayouth tests that the average leaf position offset resulting from using a Cyberknife M6 with an InCise MLC was ≤0.5 mm 24.…”
Section: Discussionmentioning
confidence: 99%